2016
DOI: 10.4191/kcers.2016.53.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nb Doping on the Dielectric and Strain Properties of Lead–free 0.94(Bi1/2Na1/2)TiO3–0.06BaTiO3 Ceramics

Abstract: ABSTRACT(Bi 1/2 Na 1/2 ) 0.94 Ba 0.06 (Ti 1-x Nb x )O 3 (BNBTxNb) ceramics were investigated in terms of the crystal structure as well as the ferroelectric, dielectric, and piezoelectric properties. While little change was observed in the microstructure except for a slight decrease in the average grain size, a significant change was noticed in the temperature dependence of dielectric and piezoelectric properties. It was shown that the property changes are closely related to the downward shift in the position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The Xray diffraction pattern of the parent BNT-BT shows the reflections around 40.2°and 46.6°with the feature of splitting of peaks, which is correlated to rhombohedral phase and tetragonal phase. 32,33 The splitting of the characteristics peaks indicates the existence of both rhombohedral and tetragonal phases in the BNT-BT8 composition. To confirm the morphotropic phase boundary in Dy doped BNT-BT8 composition, the Rietveld refinement was carried out and is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Xray diffraction pattern of the parent BNT-BT shows the reflections around 40.2°and 46.6°with the feature of splitting of peaks, which is correlated to rhombohedral phase and tetragonal phase. 32,33 The splitting of the characteristics peaks indicates the existence of both rhombohedral and tetragonal phases in the BNT-BT8 composition. To confirm the morphotropic phase boundary in Dy doped BNT-BT8 composition, the Rietveld refinement was carried out and is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…27 The first-principle calculation reported by He et al 28 demonstrates that the behaviour of the BNT-related materials may be enhanced by A-site substitution of rare-earth dopants. Various rare earth oxides such as Er 2 O 3 , 29 Gd 2 O 3 , 30 la 2 O 3 , 31 B 2 O 3 32 and Nb 2 O 5 33 have been reported for modification of piezoelectric properties of BNT-BT8 ceramics. These studies indicate that the addition of rare earth oxides controls the structural and electrical properties.…”
mentioning
confidence: 99%
“…We propose that the broadened peaks at higher values of T s in the MWS-derived ceramics may be ascribed to the improvement in density and/or grain size, which contributes to decrease the leakage current and enhances the ferroelectricity. It was also reported that the increased sintering temperature in (Na 0.5 K 0.5 )NbO 3 -based materials can enhance ferroelectricity [39] or rhombohedral symmetry in MWS-derived specimens [16,[23][24][25][26][27][28][29][30][31]. Previous studies on the effect of BaZrO 3 (BZ)-modification on the crystal structure of BNKT ceramics [32] have found that the BZ modification induces a phase transition from rhombohedral to pseudocubic symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, Biperovskite compounds have also attracted much attention as leadfree actuator materials, because of their large strains [16,[23][24][25][26][27][28][29][30][31]. The large strain observed at the normal and relaxor ferroelectric phase boundary was recently found to be closely related to the nanoscale composite of the normal and relaxor ferroelectric phases [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation